PENGARUH PENAMBAHAN KAPUR PADA SEMEN GEOPOLIMER TERHADAP MORTAR GEOPOLIMER - Ega Maryenttry; Firdaus Firdaus; Wanda Yudha Prawira (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2024)
Concrete is widely used to build infrastructure, with the increasing use of cement in Indonesia causing Portland production to increase and have a negative impact on the environment. This is because in the cement production process the combustion results release CO2 which is released directly into the air. Therefore we need another alternative that can replace cement. This study aims to analyze the effect of adding lime to geopolymer cement on geopolymer mortar. From the results of this study, the effect of the addition of lime was very influential on the compressive strength value at the age of 28 days, the addition of lime with a percentage of 1%, 2%, 3%, and 4% in each percentage at the age of the test object 28 days. The highest compressive strength value in the addition of lime was obtained at a percentage of 4% with w/c 0.30 at the age of 28 days with a compressive strength of 1.6 MPa, and in the percentage of using lime the lowest compressive strength could be at a percentage of 1% with a w/c of 0.45 with a compressive strength of 1.2 Mpa.